Adaptive Leadership: Approaches and Roles in Managing Change in an Era of Uncertainty - Treedech, Worakorn; Inphusa, Siwakorn; Hapa, Yingsan (Journal of Buddhist Education and Research (JBER), 2025)
Adaptive leadership is a crucial strategic capability in managing organizations amidst the volatility of the digital world. It focuses on analyzing and effectively responding to complex challenges through the integration of management science and art, fostering a culture of learning, and promoting continuous innovation. The main components of adaptive leadership include situational awareness, challenge identification, collaborative engagement, creating an environment conducive to change, and ongoing self-development. Leaders must cultivate essential traits such as resilience, adaptability, experiential learning, conflict management, and inspirational motivation. Strategies for developing adaptive leadership encompass systems thinking training, lifelong learning, conflict management skill development, mental resilience building, and networking to guide organizations toward success amid relentless challenges. The context of change in the digital era demands leaders who understand technology and can foster continuous innovation. Change management thus becomes an integrative process requiring understanding, flexibility, and commitment from all organizational sectors.